(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The temperature distribution inside the experimental greenhouse heated by air to air heat pumps and its impact on the growth and productivity of tomato plants were studied. Experimental greenhouse located at SIA Rītausma facility in South-East Latvia.Two commercially available regular air to air heat‑pumps with a combined heat power of 10 kW were used. To measure the temperature distribution, 18 temperature sensors with solar radiation shields at different heights and positions among the plants were installed. Additional 4 temperature sensors were used to measure the air flow temperature at the heating elements. Reference air temperature was measured at an industrial production facility heated by a common gas heating system.Temperature was found to be homogenous within 1 °C. Observed temperatures were up to 4 °C lower than set on the control unit of the heat pump. This discrepancy was compensated by higher set values for the controlling unit. As research showed the temperature stability was better than at the water-heated industrial facility at time slots when the sun was suddenly cleared from clouds.The cooling of the experimental greenhouse by air conditioning during summer time was rather challenging for the tomato plants and productivity. 23% of plant stems died until the end of the season and the yield was 50% lower than in the reference greenhouse. The energy efficiency compared to the industrial facility was approx. 8 times better and the estimated CO2 emissions were 8-16 times smaller compared to gas heating. There were no increases of heating costs determined.Further studies are needed to optimize the heating parameters and reach the desired greenhouse productivity.